DESIGN OF ELECTRONICS HARDWARE, MICROCLIMATE PARAMETERS PI CONTROL SYSTEM, GATEWAY, AND USER INTERFACE OF MICROCLIMATE CONTROL SYSTEM FOR PLANT GROWTH CHAMBER - Gemilang Suryo B., Afgantar
Experiments on plant growth that is currently often conducted without high-tech equipments causes these experiments prone to external perturbations and uncertainty of the surrounding environment, resulting in inaccurate experiment result. Furthermore, any form of recording from either plant observation or environmental condition has to be recorded manually dan observed directly on-site that can burden practitioners and researchers alike. Those problems can be mitigated with the help of an equipment with the capabilities of accurately and precisely control plant growth microclimate parameters, protected from external interference, and can be accessed remotely. To carry out its control function, the design of this equipment has to contain a processor sub-system that can undertake computation tasks based on user inputs and the condition of the surrounding environtment with an accurate and precise PI computing algorithm. To be able to be controlled by its user, the system has to contain offline access sub-system that provides interface for the user and product to be able to receive input from users dan gives important dat to the user. For remote access, the system has to be equipped with a gateway sub-system that enables the system to be connected into the internet and access the cloud. The results of processor sub-system computation is transmitted into the gateway sub-system to be saved and later transmitted into the cloud and offline access sub-system to be viewed to users. User inputs given into offline access sub-system is transmitted to the gateway sub-system which later transmitted into processor sub-system as comparator against the environment current condition. Output from processor sub-system is also used to drive the actuators. The implementation result of this system is an accurate control of parameter with error of ±1°C for temperature and ±100 lux for lighting intensity, and a system that can be accessed from directly on-site and remote.